Strengthening Character Education Through Islamic Religious Education: Analysis of Character Education Models - Krishnawati, Naniek; Nurihsan, Juntika; Budimansyah, Dasim; Nurdin, Encep Syarief (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
This study aims to look at the role of Islamic religious education in strengthening character education. The research method used in this research is descriptive qualitative with data collection techniques through interviews, observation, and group discussion forums. This research was conducted in three junior high schools in Bandung, Indonesia. The research findings show that strengthening character education is carried out using three models, namely strengthening class-based character education, strengthening school-based character education, and strengthening community-based character education. From the results of the analysis, strengthening class-based character education has been well implemented in the three schools. The stages carried out in strengthening class-based character education are the integration of strengthening character education in literacy programs, strengthening through classroom management, strengthening through learning methods, strengthening character through literacy movements, and strengthening character through classroom guidance. All of these stages have been carried out optimally in the three schools. Furthermore, strengthening school-based character education is carried out by instilling noble character values that are integrated into the culture or school rules. Strengthening school-based character education is carried out in the good category. Finally, strengthening community-based character education can be said to have not been optimally carried out properly. Strengthening community-based character education is carried out by means of school collaboration with parents, communities, and important actors in society. Strengthening community-based character is carried out in various activities such as inviting ustad to fill in religious activities, study tour activities, and practice in the community.